Leuprorelin combined with letrozole with/without everolimus in ovarian-suppressed premenopausal women with hormone receptor-positive, HER2-negative metastatic breast cancer: The LEO study. (February 2021) - Jeong, Jae Ho; Kim, Jeong Eun; Ahn, Jin-Hee; Jung, Kyung Hae; Koh, Su-Jin; Cheon, Jaekyung; Sohn, Joohyuk; Kim, Gun Min; Lee, Keun Seok; Sim, Sung Hoon; Park, In Hae; Kim, Sung-Bae
Abstract: Purpose: In the randomised phase II LEO trial, we investigated the effect of adding everolimus (EVE) to letrozole (LET) in ovarian-suppressed premenopausal women with hormone receptor-positive (HR+), HER2-negative (HER2–) recurrent/metastatic breast cancer. Methods: Patients with progression or prior exposure to tamoxifen with or without gonadotropin-releasing hormone agonists, either sequentially or concurrently, in adjuvant or metastatic setting were randomly assigned (2:1) to the EVE arm (leuprorelin + LET + EVE) or the LET arm (leuprorelin + LET) until disease progression or unacceptable toxicity. The primary end-point was progression-free survival (PFS). Secondary end-points included overall survival (OS), objective response rate (ORR), clinical benefit rate (CBR) and safety. Results: Between January 2014 and October 2018, 137 patients were enrolled (median age, 44 years [range, 24–56]). Of them, 75% had endocrine-sensitive disease, and 61% had visceral metastasis. With the median follow-up of 32.4 months, the median PFS was 18.1 months in the EVE arm and 13.8 months in the LET arm (HR 0.73, P = 0.137). Among patients with visceral metastases, the median PFS was significantly longer in the EVE arm (16.4 versus 9.5 months, P = 0.048). The median OS was not reached in both arms. The CBR was significantly higher in the EVE arm (83% versus 62%, P = 0.010). The ORR was similar between the two arms. The most common grade 3/4 adverse events in the EVE arm were neutropenia, alanine aminotransferase elevation and anaemia. Conclusions: EVE plus LET with ovarian-suppression resulted in longer PFS in tamoxifen-exposed HR+, HER2– metastatic breast cancer patients with visceral metastasis. Highlights: LEO trial assessed the effect of EVE plus LET in premenopausal HR+ breast cancer. EVE plus LET did not demonstrate improved PFS with a higher clinical benefit rate. Significant improvement in PFS was noted in patients with visceral metastases.